2014
DOI: 10.4028/www.scientific.net/amm.700.170
|View full text |Cite
|
Sign up to set email alerts
|

Improved Power Performance of Activated Carbon Anode by Fe<sub>2</sub>O<sub>3</sub> Addition in Microbial Fuel Cells

Abstract: Poor energy output and high cost are the key factors to inhibit the development and application of microbial fuel cells (MFCs). Different types of modification techniques for anode material are suggested to improve power performance in MFCs. nanoFe2O3 is characteristics of no toxicity, biocompatibility and low cost. In this work, stainless steel mesh (SSM), ultracapacitor activated carbon with SSM (AcM), Fe2O3 added AcM (AMF) anodes are investigated to improve MFCs performance. The highest maximum power densit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 14 publications
(15 reference statements)
0
2
0
1
Order By: Relevance
“…Hal ini menunjukkan bahwa selain terdapat bakteri exoelectrogen di setiap substrat, elektroda di dalam reaktor juga mampu menghantar listrik. Elektroda yang digunakan dalam penelitian ini merupakan kombinasi antara dua bahan yang telah diketahui memiliki kemampuan untuk menghantarkan elektron, yaitu stainless steel mesh dan karbon aktif (Dumas et al, 2007;Guerrini et al, 2014;Masoudi et al, 2020;Nam et al, 2018;Peng et al, 2015;Sudirjo et al, 2019;Yamashita et al, 2016;Zhao et al, 2008).…”
Section: Hasil Dan Pembahasanunclassified
“…Hal ini menunjukkan bahwa selain terdapat bakteri exoelectrogen di setiap substrat, elektroda di dalam reaktor juga mampu menghantar listrik. Elektroda yang digunakan dalam penelitian ini merupakan kombinasi antara dua bahan yang telah diketahui memiliki kemampuan untuk menghantarkan elektron, yaitu stainless steel mesh dan karbon aktif (Dumas et al, 2007;Guerrini et al, 2014;Masoudi et al, 2020;Nam et al, 2018;Peng et al, 2015;Sudirjo et al, 2019;Yamashita et al, 2016;Zhao et al, 2008).…”
Section: Hasil Dan Pembahasanunclassified
“…These include carbon cloth, carbon paper, or sheet or graphite plates and graphite rod. Using carbon-based anode materials has the advantages of cost-effectiveness, biocompatible nature, efficient electrical conductivity, and chemical stability [73]. Due to their potentially high-performance enhancement and excellent properties, these have been recognized as being very useful for building MFCs.…”
Section: Modern Carbon-based Anodesmentioning
confidence: 99%
“…Tafel's electrochemical extrapolation technique showed that MFC anode oxidation activation was stronger when Fe 2 O 3 was added. The authors attribute the increase in kinetic activity to the facilitated extracellular electron transfer from the cell to the bacteria, showing that the rate of anode electron transfer can be increased by the addition of Fe 2 O 3 [12]. Sayed et al [13] found that a carbon cloth (CC) anode covered with Fe nanostructures had a lower potential than an unmodified anode (−0.01 and 0.16 V vs. Ag/AgCl, respectively).…”
Section: Introductionmentioning
confidence: 99%